Especies de picudos (Coleoptera: Curculionidae) asociados a limón persa en Tabasco, México - Sumano-López, Dante; Wallace-Jones, Robert; Sánchez-Soto, Saúl; Bautista-Martínez, Nestor; Ortiz-García, Carlos Fredy; García-López, Eustolia; Ramos-Hernández, Eder; Sol-Sánchez, Ángel (Instituto de Ecología, A.C., 2023)
Weevils (Coleoptera: Curculionidae) are one of the main pests in citrus production systems due to their distribution and way of feeding. The objective of this work was to morphologically identify the species of weevils associated with the cultivation of Persian lime (Citrus latifolia Tanaka) in the citrus zone of the municipality of Huimanguillo, Tabasco, Mexico. The captures of weevils were made directly in the canopy, from September 2019 to February 2021, for a total of 17 collected in three Persian lemon plantations, two with conventional management and one with organic management, each one with useful plots of two hectares (624 plants). A total of 1,039 weevils corresponding to four morphospecies were collected, of which 240 were morphologically identified as Epicaerus sp. (1), 355 as Epicaerus sp. (2), 112 as Exophthalmus opulentus and 332 as Cleistolophus subfasciatus.